The absence of the caffeine synthase gene is involved in the naturally decaffeinated status of Coffea humblotiana, a wild species from Comoro archipelago - Nathalie Raharimalala (Nature Portfolio, 2021)
Abstract Caffeine is the most consumed alkaloid stimulant in the world. It is synthesized through the activity of three known N-methyltransferase proteins. Here we are reporting on the 422-Mb chromosome-level assembly of the Coffea humblotiana genome, a wild and endangered, naturally caffeine-free, species from the Comoro archipelago. We predicted 32,874 genes and anchored 88.7% of the sequence onto the 11 chromosomes. Comparative analyses with the African Robusta coffee genome (C. canephora) revealed an extensive genome conservation, despite an estimated 11 million years of divergence and a broad diversity of genome sizes within the Coffea genus. In this genome, the absence of caffeine is likely due to the absence of the caffeine synthase gene which converts theobromine into caffeine through an illegitimate recombination mechanism. These findings pave the way for further characterization of caffeine-free species in the Coffea genus and will guide research towards naturally-decaffeinated coffee drinks for consumers.